A detailed implementation of multithreading and out-of-core computation to the conventional boundary element algorithm with minimum code changes - de Souza Schiara, Leandro (2023)
The boundary element method (BEM) poses some significant advantages over other numerical methods. Nevertheless, the generation of fully populated unsymmetrical matrices can induce some important problems for the conventional BEM algorithm concerning memory limitations. Furthermore, special integration procedures are used in BEM demand substantial computational power, and these characteristics can compromise BEM applicability for large problems unless more sophisticated approaches are used. A relatively straightforward way to extend BEM usability is to employ multithreading and out-of-core capabilities. This work presents detailed algorithms that can be easily implemented in conventional BEM codes. The improvements obtained are evaluated and commented.